Assisted color acquisition for 3D models. (November 2017) - Coutinho, Daniel; Marroquim, Ricardo; Dellepiane, Matteo; Scopigno, Roberto
Highlights: Immediate feedback of material acquisition. Per-vertex material reflectance representation. Assisted acquisition for in situ digitization campaigns. Good diffuse color with specular approximation. Graphical abstract: Abstract: Capturing surface appearance precisely is paramount for modeling realistic materials. Nevertheless, the spatially varying nature of most materials is difficult to measure. State-of-the-art methods often rely on complex apparatus and controlled environments, and even if they are able to acquire reliable SVBRDFs, the whole process usually takes a long time and generates a large amount of data, that is often redundant. In this work, we propose a method for fast and assisted acquisition of material properties on-site. The system has a simple setup, requiring only a generic camera and a light source. Consequently, it is also very portable and appropriate for a broad range of object sizes and scenarios. The system guides the acquisition process, allowing for a fast capture session while at the same time producing high-quality per vertex diffuse colors. To help in achieving a complete coverage it suggests missing light directions, reducing the amount of necessary input images and the acquisition time. The system is designed to work in situ, therefore the whole acquisition process works with immediate feedback and interactive integration of new data. We show results for a variety of objects differing in size and materials.